Development and Optimization of Solid Self-Nanoemulsifying Drug Delivery System (Solid-SNEDDS) for Enhancing Oral Bioavailability of Poorly Water-Soluble Itraconazole. - Albhar, Ketan; Kasabe, Amit; Wagh, Vaibhav (Journal of Neonatal Surgery, 2025)
This study aimed to develop and optimize a Solid-Self Nanoemulsifying Drug Delivery System (Solid-SNEDDS) to enhance the solubility, dissolution rate, and bioavailability of itraconazole. The optimized formulation (SF1) was prepared using Capmul MCM, Tween 20, and Propylene Glycol as excipients. Solubility studies indicated the highest solubility in Capmul MCM (8.7 mg/ml). SF1 demonstrated a drug content of 95.15% ± 0.12 and an entrapment efficiency of 89.56% ± 0.12, suggesting efficient drug loading and minimal leakage. In vitro dissolution studies showed a maximum drug release of 98.82% at 8 hours, surpassing the marketed formulation's 98.5%. Particle size analysis revealed a mean size of 95.2 nm with a PDI of 0.115, indicating uniform distribution, while a zeta potential of -29.3 mV suggested good colloidal stability. FTIR and DSC analyses confirmed the stability and compatibility of formulation components. Stability studies over three months indicated no significant changes in drug content, entrapment efficiency, or drug release. The results suggest that the optimized Solid-SNEDDS formulation significantly improves the solubility and bioavailability of itraconazole, offering a promising strategy for the oral delivery of lipophilic drugs.